Soil health assessment after 40 years of conservation and conventional tillage management in Southeastern Coastal Plain soils. Issue 4 (24th May 2021) - Ye, Rongzhong; Parajuli, Binaya; Szogi, Ariel A.; Sigua, Gilbert C.; Ducey, Thomas F.
Abstract: Conservation tillage (CST) and cover crops are important components of soil health management. In the present study, we applied two independent soil health assessment approaches to evaluate the impacts of 40‐yr CST and additional 4‐yr cover cropping on a range of soil health indicators and the overall soil health in typical southeastern Coastal Plain soils. Soils were collected at 0–15 cm and analyzed for physical, chemical, and biological indicators. The Soil Management Assessment Framework (SMAF) and Cornell's Comprehensive Assessment of Soil Health (CASH) were used to calculate soil health indices. When compared to conventional tillage, 40‐yr CST increased active carbon (C) from 301 to 420 mg kg –1 and organic nitrogen (N) mineralization potentials from 0.78 to 0.91 mg kg –1 d –1, but it reduced soil electrical conductivity from 133 to 101 μs cm –1 . No difference in soil aggregate stability, total C, extractable phosphorous and potassium, microbial biomass C, respiration, and glucosidase activities were observed between the two tillage treatments. Cover cropping had no impacts on any measured variables, except that it increased soil total N. Regardless of tillage and cover cropping, both the SMAF and CASH scoring functions suggested no changes in overall soil health. Soil organic C (SOC) was the only indicator positively correlated with both the SMAF and CASH indices, indicating its importance in maintaining the health of the tested soils. Moreover, CASH index recommended improving soil structure and SOC as the management priority to maintain or improve the overall soil health. Increasing organic inputs along with CST is seemingly the optimal management option. Core Ideas: Two soil health assessment indices were used to evaluate management impacts, Forty‐year conservation tillage did not improve overall health indices of a sandy soil (0–15 cm). Inclusions of 4‐yr cover cropping did not improve indices outcomes but increased soil total N. Soil organic C was the only measured variable correlated with both soil health indices. Improving soil structure and organic carbon content remain the management priorities.